2014
DOI: 10.5489/cuaj.2054
|View full text |Cite
|
Sign up to set email alerts
|

Application of bone scans for prostate cancer staging: Which guideline shows better result?

Abstract: Cite as: Can Urol Assoc J 2014;8(7-8):e515-9. http://dx.doi.org/10.5489/cuaj.2054 Published online August 11, 2014. AbstractIntroduction: We evaluated the accuracy of current guidelines by analyzing bone scan results and clinical parameters of patients with prostate cancer to determine the optimal guideline for predicting bone metastasis. Methods: We retrospectively analyzed patients who were diagnosed with prostate cancer and who underwent a bone scan. Bone metastasis was confirmed by bone scan results with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…However, values between 10 and 20 remain in the gray zone. 8 NICE guidelines (updated on December 15, 2021) added another group of patients to whom an isotope bone scan should not be routinely offered. Namely Cambridge prognostic group 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, values between 10 and 20 remain in the gray zone. 8 NICE guidelines (updated on December 15, 2021) added another group of patients to whom an isotope bone scan should not be routinely offered. Namely Cambridge prognostic group 2.…”
Section: Discussionmentioning
confidence: 99%
“…Also there is no debate about PSAs less than 10 or more than 20. However, values between 10 and 20 remain in the gray zone 8 …”
Section: Discussionmentioning
confidence: 99%
“…The risk profile in our study included low-, intermediate-, and high-risk patients. Although the use of 99m Tc-PSMA is mostly reserved for detection of occult disease in patients with low PSA 41 , 42 and primary staging of high-risk patients 43 , 44 and bone scan to intermediate- to high-risk patients, 12 we were also interested in seeing how 99m Tc-PSMA performs in patients across the risk spectrum, including patients typically reserved for staging bone scan. 6 Thomsen et al 45 reported a correlation between advanced disease stage and high PSA with bone metastases, and we report similar findings with patients having advanced disease stage and a high PSA more likely to have metastases on both 99m Tc-PSMA and 99m Tc-MDP scans and with the 2 methods having no statistically significant difference in detection rate (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…No study has evaluated the relationship of bone metastasis in PCa and PNI in biopsy yet. In almost all PCa guidelines, bone scan is indicated for the evaluation of skeletal metastasis . Prediction of bone metastasis is also generally based on tPSA level, GS and stage of the disease in almost all of the PCa guidelines.…”
Section: Discussionmentioning
confidence: 99%